2005
DOI: 10.1177/0361198105191800113
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impacts of Speed Reduction Technologies

Abstract: This paper presents the results of a quantitative and qualitative evaluation of a dynamic curve warning system deployed at one site on Interstate 5 in Oregon. On a dynamic message sign, the system displays messages directed to drivers on the basis of the observed speed of approaching vehicles. For the evaluation, three measures of effectiveness were selected: ( a) the change in mean speed for passenger cars and commercial vehicles, ( b) the change in the speed distribution for both passenger cars and trucks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Researchers also evaluated the effects of DSFS on drivers of different vehicles, primarily cars and trucks. Several studies found no significant differences in speed reduction between cars and trucks [4,11,18]. Some studies found that the effect of speed reduction was greater for passenger cars than for other vehicles (heavy vehicles) [1,6,9], while several recent studies found that DSFS had greater effects on drivers of heavy vehicles [7,26,42].…”
Section: Effect Of the Vehicle Typementioning
confidence: 99%
See 3 more Smart Citations
“…Researchers also evaluated the effects of DSFS on drivers of different vehicles, primarily cars and trucks. Several studies found no significant differences in speed reduction between cars and trucks [4,11,18]. Some studies found that the effect of speed reduction was greater for passenger cars than for other vehicles (heavy vehicles) [1,6,9], while several recent studies found that DSFS had greater effects on drivers of heavy vehicles [7,26,42].…”
Section: Effect Of the Vehicle Typementioning
confidence: 99%
“…In 2006, Monsere et al examined two overhead DSFSs on a horizontal curve on the interstate in a before-and-after study [18]. The overhead sign indicated the highest speed within the detection zone.…”
Section: Garbermentioning
confidence: 99%
See 2 more Smart Citations